An Individual Rehabilitation and/or Habilitation Program for Children with Disabilities (IPRH) - KA, Shapovalov; LA, Shapovalova; NG, Knyazeva; G Yu, Pokhodyaeva; VS, Toropova; LА, Sannikova; AS, Mezentseva (Journal of Advanced Pediatrics and Child Health, 2024)
Introduction: The individual program of rehabilitation and (or) habilitation of children with disabilities (IPRH) is mandatory for execution by the relevant state authorities, local self-government bodies, as well as organizations regardless of organizational-legal forms and forms of ownership. Objective: To conduct a pilot analysis of the implementation of the IPRH contingent of patients of children with disabilities in an urban children’s clinic. Patients and methods: There were 366 reports on the implementation of measures provided for by an IPRH for a disabled person (disabled child) of 222 disabled. The organization of the study was in the nature of a continuous sample. The criterion for the inclusion of patients in it was the passage of an IPRH in a disabled child within a specified time frame. The following techniques were used: grouping, absolute and relative values, average values, detailing, and generalization. The threshold error probability for statistically significant differences was set at a level of 0.05. Results: The structure of the results of the control of the performance of IPRH in 222 disabled children according to the classes of diseases that caused the onset of disability (ICD) was as follows 1) G00-G99 - 35.47 ± 3.13%; 2) Q00-Q99 - 23.50 ± 2.77%; 3) 11.11 ± 2.05%; 4) C00-D48 - 10.25 ± 1.98%; 5) H60-H95 - 7.26 ± 1.67%; 6) M00-M99 - 2.99 ± 1.11%; 7-8) H00-H59 and P00-P96 - 2.14 ± 0.95%; 9-10) K00-K93 and S00-T98 - 1.29 ± 0.74% each; 11-12) I00-I99 and N00-N99 - 0.85 ± 0.60% each; 13-14) J00-J99 and L00-L99 - 0.43 ± 0.42% each. Conclusion: 1. In the structure of IPRH in 222 disabled children, according to the classes of diseases that caused disability (ICD), the following prevailed: 1) VI Diseases of the nervous system G00-G99 – 35.47%; 2) XVII Congenital anomalies, chromosomal disorders Q00-Q99 - 23.50%; 3) IV Diseases of the endocrine system, nutritional disorders, and metabolic disorders E00-E90 – 11.11%; 4) II Neoplasms C00-D48 - 10.25%; 5) VIII Diseases of the ear and mastoid process H60-H95 - 7.26%; 6) XIII Diseases of the musculoskeletal system and connective tissue M00-M99 - 2.99%; 7-8) VIII Diseases of the ear and mastoid process H60-H95 and VII Diseases of the eye and its adnexa H00-H59 - 2.14% each. 2. The effectiveness of medical rehabilitation of disabled children was as follows: 1) Improvement - 23.26%; 2) Stabilization - 74.88%; 3) Deterioration - 1.86%. Dynamic observation was carried out on 94.26% of disabled children, drug therapy - 77.32%, non-drug therapy - 66.93%, and other types of medical rehabilitation were received by 14.48% of patients. Reconstructive operations were performed on 11.26% of disabled children. 3. Prosthetics and orthotics were performed on 38.74% of disabled children. 32.43% of disabled children in need received sanatorium treatment, and 30.18% are currently in line to receive a voucher. For various reasons, 24.32% refused this type of rehabilitation; 3.60% of patients had contraindications at the time the voucher was provided. 4. The obtained research results become the initial everyday statistical tool for objectifying the process of rehabilitation of patients and determining the strength and means of a medical institution to monitor and successfully implement an individual rehabilitation/habilitation program for a disabled person.